2017
DOI: 10.3168/jds.2017-12998
|View full text |Cite
|
Sign up to set email alerts
|

A 100-Year Review: A century of dairy heifer research

Abstract: The years 1917 to 2017 saw many advances in research related to the dairy heifer, and the Journal of Dairy Science currently publishes more than 20 articles per year focused on heifers. In general, nutrition and management changes made in rearing the dairy heifer have been tremendous in the past century. The earliest literature on the growing heifer identified costs of feeding and implications of growth on future productivity as major concepts requiring further study to improve the overall sustainability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 179 publications
0
30
0
2
Order By: Relevance
“…Rather than viewing an individual calf death as a demoralizing end-point, the narrative provides an understanding from which to elicit change across the population. Rearing dairy replacement heifers should focus on limiting environmental impact, protecting animal welfare, and minimizing required inputs while returning the most profitable outputs (Hoffman and Funk, 1992;Heinrichs et al, 2017). As such, reducing economic costs and impairment to animal welfare through improved understanding of dairy calf mortality provides a critical control point for accelerating whole-farm efficiency and sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than viewing an individual calf death as a demoralizing end-point, the narrative provides an understanding from which to elicit change across the population. Rearing dairy replacement heifers should focus on limiting environmental impact, protecting animal welfare, and minimizing required inputs while returning the most profitable outputs (Hoffman and Funk, 1992;Heinrichs et al, 2017). As such, reducing economic costs and impairment to animal welfare through improved understanding of dairy calf mortality provides a critical control point for accelerating whole-farm efficiency and sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Heifer raising equals to 15% to 20% of the total cost of milk production, thereby representing the second largest share among the cost factors, following feed costs [1]. The aim of the dairy farm managers is to minimize the costs and maximize the future revenue of dairy heifers, however, modern objectives also include environmental impact and animal welfare considerations [2]. Therefore, those factors that are related to the performance of replacement heifers are relevant from an economic point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, earlier studies have shown that the AFC may substantially contribute to the total rearing costs [18,19]. We observed substantial differences in the AFC between visited farms and given the median AFC of 802 days; our findings suggest that some of the visited dairy farmers might be affected by some economic burden due to the elevated median AFC in relation with the general goal at 22 to 24 months (730 days) [20,21].…”
Section: Discussionmentioning
confidence: 45%